PENGARUH KEPUASAN KERJA TERHADAP KINERJA KARYAWAN MELALUI KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING - Saifullah, Ahmad; aspiannor, akhmad; Asnawi, Asnawi; Dewi, Tusiana (LPPM Politeknik Pratama, 2023)
The findings of this study indicate that job satisfaction has a positive effect on organizational commitment. Furthermore, organizational commitment also has a positive impact on employee performance at Q Mall Banjarbaru. These findings suggest that organizational commitment plays a crucial role in connecting job satisfaction with employee performance. The managerial implications of this study are that Q Mall management needs to pay attention to job satisfaction and make efforts to enhance employees' organizational commitment to improve their performance.This research contributes both theoretically and practically to expanding the understanding of the relationships among job satisfaction, organizational commitment, and employee performance.